A Language to be Heard: Andwa Leaders and the Enactment of Linguistic Citizenship in the Ecuadorian Amazon - Rosado, Erika (2024)
In 2003, the Andwa Nationality of Ecuador emerged as a distinct ethnic group, organized around an extinct language known as Katsakati. Since then, Andwa leaders have established linguistic reinsertion as the main political and cultural project of their communities. Drawing on the ethnographic method and critical analysis of interviews, this article explores how Andwa leaders deploy linguistic resources associated with Katsakati, along with other symbolic means, to assert their authenticity in front of other Indigenous actors who question their identity claims. The author interprets these efforts as acts of “linguistic citizenship,” as they show how linguistic resources, may be mobilized by historically marginalized peoples to claim agency and address inequalities in postcolonial contexts.